PENGARUH LIVE STREAMING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION DI TIKTOK SHOP (STUDI KASUS PADA GEN Z DI SUMBAWA BESAR) - Arya Rifki Salsa Bila; Tomy Dwi Cahyono (Publika Citra Media, 2026)
This study aims to analyze the influence of live streaming and online customer reviews on purchasing decisions of fashion products on TikTok Shop among Generation Z consumers in Sumbawa Besar. The research method used is a quantitative approach with data collected through questionnaires distributed to 100 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that both live streaming and online customer reviews have a positive and significant influence on purchasing decisions, both partially and simultaneously. This research provides implications for business actors to optimize live streaming utilization and consider customer reviews to improve purchase conversion.